Analiza językowa tekstu prawniczego - Michalewski, Kazimierz (Poznańskie Spotkania Językoznawcze, 2014)
It is an analysis of the grounds of a certain court order. The text contains numerous linguistic deficiencies. Among them are: typing errors, spelling mistakes, punctuation, flexographic, lexical and syntactical errors. Undeniably they harm the prestige of the office which signed the document and make it more difficult to interpret the decisions of such an office. Albeit the result of the analysis of one legal writing does not entitle to making generalizations, however it encourages linguists to become interested in this category of speech.